RISK FACTORS FOR THE EARLY NEONATAL MORTALITY IN NEWBORNS WITH VERY LOW AND EXTREMELY LOW BIRTH WEIGHT - О. V. Lebedeva; Т. А. Chikina ("Paediatrician" Publishers LLC, 2014)
Objective: Our aim was to assess the association of perinatal factors with the early neonatal mortality in newborns with very low (VLBW) and extremely low birth weight (ELBW).Methods: The statistical data was carried out, that is analysis of 17 perinatal factors of 28 newborns with an ELBW with gestation of 23-27 weeks and 18 newborns with a VLBW with gestation of 28-32 weeks, who died in the first 7 days of life. The comparison group consisted of 25 newborns with an ELBW and 56 children with a VLBW with gestation of 25-27 and 28-32 weeks, respectively, who survived the early neonatal period. The association of risk factors with the early neonatal mortality was assessed by means of a multiple-factor logistic regression analysis. A critical p error level was set equal to 0.05. Results: In newborns with a VLBW the increased risk of the early neonatal mortality depended on a gestation term (OR 4.40, 95% CI 1.56-11.71; р = 0.002) and emergency Caesarean section (OR 7.48, 95% CI 1.28-43.74; р = 0.008). A vaginal birth increased the survival chance (OR 0.12, 95% CI 0.01-0.86; р = 0.032). Newborns with an ELBW had the following factors of the increased risk of the early neonatal mortality: gestational age (OR 2.86, 95% CI 1.06-7.73; р = 0.038), Apgar score at the 5th minute (OR 1.91, 95% CI 0.99-3.69; р = 0.050) and presence of chorioamnionitis (OR 5.45, 95% CI 1.0-29.53; p = 0.048). An elective Caesarean section increased the survival chance (OR 0.02, 95% CI 0.001-0.44; p = 0.048). Conclusion: Summarizing the obtained data, we can conclude that besides a gestational age the risk of early neonatal mortality in newborns with a VLBW may be increased due to the emergency Caesarean section, with an ELBW - due to a low Apgar score at the 5th minute and the presence of mother's chorioamnionitis. A vaginal birth in newborns with a VLBW and an elective Caesarean section in children with an ELBW increase survival chances.